1999
DOI: 10.1007/s001470050191
|View full text |Cite
|
Sign up to set email alerts
|

Kidney preservation in the next millenium

Abstract: For the past decades, severe hypothermia has represented the foundation of organ preservation in clinical transplantation. Beneficial as hypothermia has proven to be in preserving grafts from heart-beating donors, hypothermia does not seem to provide the window necessary for the prospective evaluation of organ function. With the increasing use of non-heart-beating donors, it is logical to propose that if organs are to be evaluated prospectively, it will be necessary to preserve them at warmer temperatures. Sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Several studies have shown that NMP is superior to HMP or CS preservation of severely WI-damaged NHB donor kidneys [72][73][74][75][76][77]. Moreover, NMP may offer a more reliable method for ex vivo pretransplant functional assessment of a kidney graft based on urine production, perfusion dynamics and biochemical injury markers in the perfusate [78]. Ex vivo functional assessment of NHB pulmonary grafts, as proposed by several groups, also depends on adequate NMP, combined with artificial ventilation [79,80].…”
Section: Preservation Techniquesmentioning
confidence: 99%
“…Several studies have shown that NMP is superior to HMP or CS preservation of severely WI-damaged NHB donor kidneys [72][73][74][75][76][77]. Moreover, NMP may offer a more reliable method for ex vivo pretransplant functional assessment of a kidney graft based on urine production, perfusion dynamics and biochemical injury markers in the perfusate [78]. Ex vivo functional assessment of NHB pulmonary grafts, as proposed by several groups, also depends on adequate NMP, combined with artificial ventilation [79,80].…”
Section: Preservation Techniquesmentioning
confidence: 99%
“…For the past decades, severe hypothermia has also represented the foundation of kidney preservation in clinical transplantation, although some authors have advocated the use of more moderate levels of hypothermia to prevent ischemic damage during transplantation (8).…”
mentioning
confidence: 99%
“…Another approach to stimulate anabolic metabolism during preservation in order to prolong adequate preservation time, could be the perfusion of organs at warmer temperatures [28]. In an environment where renal metabolism is continuously supported instead of inhibited, and waste products are removed, the limitations of static storage may be avoided.…”
Section: Effect Of CI On Organ Functionmentioning
confidence: 99%